Website-Based Baduy Tourism Information System Using The Software Development Life Cycle Method - Adinda, Putri; Eviliana, Devita; Rukhviyanti, Novi (INOVTEK Polbeng - Seri Informatika, 2025)
Baduy cultural tourism has great potential, but limited information and a manual ticket booking system result in long queues and inadequate tourism services. This study aims to develop a Web-based Baduy Tour Ticket Booking Information System using the Software Development Life Cycle method for tourist ticket reservations using the waterfall method approach. System development includes needs analysis, system design, implementation, testing, and maintenance. The assessment of the system is carried out through functional testing and black-box testing methods to ensure the legality and confidentiality of the application. The development of this system utilises Laravel as its full-stack framework, which includes Javascript, PHP, blade and CSS with Bootstrap. The test results showed that the system was able to save reservation time by up to 60% compared to the manual method, and from the 50 users surveyed, the customer satisfaction rate was 85%. Thus, the development of the Tourism Information System provides a more effective and efficient solution to help Buduy's cultural tourism.